Assessing the flood risk to evacuees in outdoor built environments and relative risk reduction strategies. (October 2021) - Bernardini, Gabriele; Finizio, Fiorenza; Postacchini, Matteo; Quagliarini, Enrico
Abstract: Climate-change induced disasters, like floods, are expected to increase in the future. In outdoor built environments, flood risk to evacuees depends on interactions between floodwater spreading, built environment features, flood-induced modifications, and individuals' reaction in emergency phases. Disaster risk reduction strategies should mitigate the immediate flood impacts and improve the community resilience, while being easy-to-implement and effectively supporting evacuees during the initial phases of the emergency. Simulation-based methodologies could support safety planners in evaluating the effectiveness of such strategies, especially if basing on a micro-scale-oriented approach that represents emergency interactions between each individual and the surrounding outdoor built environment. This study adopts an existing micro-scale simulator (FlooPEDS) reproducing experimental-based flood evacuation behaviours. According to a behavioural design-based approach, simulation results focus on individual responses in the outdoor built environment through Key Performance Indicators (KPIs) aimed at providing evidence of critical interactions between evacuees, floodwaters and the outdoor built environment. A case study is selected by considering different flood scenarios to test such KPIs. Risk reduction solutions are then provided, and their effectiveness is checked by simulations. Results show the micro-scale and behavioural design-based approach capabilities in proposing multi-scenarios solutions (e.g.: architectural elements to support evacuees; emergency planning). Highlights: Flood risk evaluation and reduction in outdoor built environments are investigated. The proposed behavioural design-based approach jointly considers evacuation and hydrodynamic scenarios. Novel Key Performance Indicators are proposed. Such approach is applied to a significant case study. Risk reduction strategies are proposed and their effectiveness evaluated.